1984
DOI: 10.3758/bf03333746
|View full text |Cite
|
Sign up to set email alerts
|

Creation of the horizontal-vertical illusion through imagery

Abstract: Perception of the horizontal-vertical illusion was examined as a function of imaging ability. Subjects who scored either high or low on this attribute (as assessed by the Vividness of Visual Imagery Questionnaire, or VVIQ) were asked to image an inducing line or lines of the illusory stimulus. High imagers reported perceiving the illusion whether the inducing line(s) were imaged or were physically present. Also, the magnitude of the illusion as created by imagery-induced lines was equivalent to that produced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
2
22
1
Order By: Relevance
“…In our procedure , subjects who imagined the configuration of a standard geometric illusion did not yield a reliable illusory effect. This was true for both subjects with vivid visual imagery and subjects without vivid imagery, results that are in clear contrast to data reported by Wallace (1984aWallace ( , 1984b.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our procedure , subjects who imagined the configuration of a standard geometric illusion did not yield a reliable illusory effect. This was true for both subjects with vivid visual imagery and subjects without vivid imagery, results that are in clear contrast to data reported by Wallace (1984aWallace ( , 1984b.…”
Section: Discussioncontrasting
confidence: 99%
“…The flaw in this argument lies in its premise : the suggestion that these extraneous factors were equivalent for high-and low-vividness subjects . In all of Wallace's (1984aWallace's ( , 1984b) studies, subjects were asked whether they were " able to see" the line(s) specified by the experimenter, whether they were able to "produce" or "conjure up" the relevant line. If the subject responded "yes" to this question, he/she was asked about the relative lengths of the figure's lines; if the subject responded "no" to the question, the procedure ended.…”
Section: /\/\ A/\mentioning
confidence: 99%
“…However, amodal completion in a perceptual process occurs automatically in a very limited amount of time. Above all, it was demonstrated that the HV illusion also occurs when participants are simply required to imagine the two lines [16,22], showing that it is the mental representation of the stimuli, rather than the physical stimulation per se, that seems to count more for the emergence of this size illusion. Provided that it is hard to simultaneously represent two objects in the same portion of space and at the same distance from the observer, there is a concrete possibility that participants represent the two lines at different distances, with Petter's rule guiding them in establishing which line is behind the other.…”
Section: Discussionmentioning
confidence: 99%
“…No such improvements occur among weak imagers or among those who cannot control their images. Again, Wallace (1984) found that those with vivid visual imagery, but not those with weak visual imagery, experience the horizontal-vertical illusion when physically presented with one of the lines (either horizontal or vertical) and when they are asked to project a visual image of whichever line is missing.…”
Section: Downloaded By [University Of Nebraska Lincoln] At 19:45 04 mentioning
confidence: 96%